Physiological and biochemical aspects of hydroxylations and demethylations catalyzed by human 2-oxoglutarate oxygenases. - Loenarz, C; Schofield, C (2011)
Pioneering work in the 1960s defined prolyl and lysyl hydroxylations as physiologically important oxygenase-catalyzed modifications in collagen biosynthesis; subsequent studies demonstrated that extracellular epidermal growth factor-like domains were hydroxylated at aspartyl and asparaginyl residues. More recent work on the hypoxia-sensing mechanism in animals has shown that prolyl and asparaginyl hydroxylation of the hypoxia-inducible transcription factor play central roles in sensing hypoxia, by regulating protein-protein interactions in an oxygen-dependent manner. The collective results imply that protein hydroxylation is more common than previously perceived. Most protein hydroxylases employ Fe(II) as a cofactor, and 2-oxoglutarate and oxygen as co-substrates. Related enzymes catalyze the demethylation of N(ɛ)-methyl lysine residues in histones and of N-methylated nucleic acids, as well as hydroxylation of 5-methyl cytosine in DNA and 5-methoxycarbonylmethyluridine at the wobble position of tRNA. The combination of new molecular biological and analytical techniques is likely to reveal further roles for oxygenase-mediated modifications to biomacromolecules.